I’d rather have the girls eat first: a mixed-methods study on the nutritional health of migrant children in Chile - Teresita Rocha-Jimenez; CARREÑO CALDERON, ALEJANDRA ANGELICA; Janeth Solís de Ovando Calderón; Nicole Silva-Moreno; Marcela Oyarte; Maria Consuelo Robledo (Frontiers Media SA, 2026)
Introduction Child malnutrition remains a persistent global challenge, disproportionately affecting migrant populations who experience barriers to health, food access, and social protection. In Chile, increasing migration from Latin America and the Caribbean (LAC) has reshaped the country’s nutritional landscape, revealing structural inequalities in child health. This study examines the nutritional status and food security of migrant children and adolescents in Chile, investigating how structural and cultural factors influence their access to adequate food and nutrition. Methods A convergent mixed-methods design integrated quantitative analyses of national datasets, the National Socioeconomic Characterization Survey (CASEN 2022) and the Ministry of Health’s Monthly Statistical Records (REM 2019–2021) with 42 qualitative interviews conducted in 2023 with migrant caregivers and primary healthcare professionals across the regions of Tarapacá, O’Higgins, and Metropolitan Santiago. Quantitative analyses were conducted to describe nutritional status, food insecurity (using the ELCSA scale), and participation in school feeding programs (as measured by the JUNAEB). Qualitative data were thematically analyzed to capture the lived experiences of food access, healthcare, and cultural adaptation. Results Quantitative findings revealed that migrant children exhibit lower rates of overweight and obesity, but a higher prevalence of undernutrition (2.9%) compared to Chilean peers (1.4%). Severe food insecurity affects 28.1% of migrant households, nearly double the rate among Chileans (15.9%). Qualitative findings highlight precarious living conditions, informal employment, and limited access to potable water and cooking facilities as barriers to adequate nutrition. Administrative restrictions linked to irregular migration status also hinder access to public food programs. Furthermore, cultural discrepancies between Chilean dietary guidelines and migrant food practices limits adherence and reinforces exclusion. Discussion The study exposes a “double nutritional vulnerability” among migrant children, undernutrition arising from deprivation and potential overnutrition through dietary acculturation. These findings underscore the need for a dual-focus policy approach that ensures equitable access to nutrition and incorporates intercultural perspectives into child health programs. Expanding school feeding coverage regardless of migration status and culturally adapting nutritional interventions are essential steps toward reducing structural food insecurity and advancing child health equity in Chile.